2020
DOI: 10.3389/fmolb.2020.00122
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Pathway, Genome Stability and Cancer

Abstract: The acquisition of genomic instability is one of the key characteristics of the cancer cell, and microsatellite instability (MSI) is an important segment of this phenomenon. This review aims to describe the mismatch DNA repair (MMR) system whose deficiency is responsible for MSI and discuss the cellular roles of MMR genes. Malfunctioning of the MMR repair pathway increases the mutational burden of specific cancers and is often involved in its etiology, sometimes as an influential bystander and sometimes as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
160
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 102 publications
(146 reference statements)
0
160
0
3
Order By: Relevance
“…DNA double-strand breaks (DSBs) are genomic lesions that may lead to carcinogenesis if left unrepaired or not properly repaired. The major pathways participating in DNA damage detection and repair are: (i) the nucleotide excision repair (NER) pathway, involved in eliminating bulky adducts; (ii) the mismatch repair (MMR) involved in recognition of errors occurring during DNA replication and homologous recombination (HR) or non-homologous end joining (NHEJ), eventually recognizing and repairing DSBs; (iii) the base excision repair (BER) pathways, involved in oxidative damage to DNA bases and single-strand breaks (SSBs) [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Dna Repair and Cellular Transformationmentioning
confidence: 99%
“…DNA double-strand breaks (DSBs) are genomic lesions that may lead to carcinogenesis if left unrepaired or not properly repaired. The major pathways participating in DNA damage detection and repair are: (i) the nucleotide excision repair (NER) pathway, involved in eliminating bulky adducts; (ii) the mismatch repair (MMR) involved in recognition of errors occurring during DNA replication and homologous recombination (HR) or non-homologous end joining (NHEJ), eventually recognizing and repairing DSBs; (iii) the base excision repair (BER) pathways, involved in oxidative damage to DNA bases and single-strand breaks (SSBs) [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Dna Repair and Cellular Transformationmentioning
confidence: 99%
“… 4 The MMR system is composed of a set of proteins that interact as heterodimers to sense and repair unpaired bases and small loops formed by insertions or deletions. 5 These components are encoded by 8 genes, including hMSH2, hMSH3, hMSH5, hMSH6, hMLH1, hPMS1 (hMLH2), hMLH3, hPMS2 (hMLH4). 6 8 In the absence of a functional MMR system, the insertion-deletion mutation was not repaired, resulting in a new allele with a length change.…”
Section: Introductionmentioning
confidence: 99%
“…MMR plays a crucial role in regulating tumor gene mutation 37 . The abnormal expression of MMR-related proteins is also related to tumor drug resistance 38 . In the case of leukemia, Diouf et al observed that the protein level of DNA mismatch repair protein MSH2 in 11% of childhood acute lymphoblastic leukemia cells decreased significantly and was resistant to mercaptopurine 39 .…”
Section: Discussionmentioning
confidence: 99%